2015
DOI: 10.1159/000376581
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Morbidity due to Compound Mandibular Body Fractures: Does It Have a Relationship with Treatment Outcome?

Abstract: Objective: The aim of this study was to evaluate the relationship between the degree of preoperative pain and trismus with the development of complications following the repair of isolated unilateral compound mandibular body fractures using a closed reduction technique. Subjects and Methods: This was a 7-year prospective study carried out at the Dental and Maxillofacial Surgery Clinic of the University of Calabar Teaching Hospital, Calabar, Nigeria. Of a total of 97 patients, 83 (85.6%) subjects (66 males, 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The majority of patients suffered a low degree of posttraumatic pain and a small interincisal distance. The postoperative pain and trismus are related to the inflammatory response associated with the mandibular injury [15]. The degree of symptoms such as edema, pain, and trismus depends on the force delivered to the face and the extent of inflammation associated with the trauma, resulting in varying levels of these clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients suffered a low degree of posttraumatic pain and a small interincisal distance. The postoperative pain and trismus are related to the inflammatory response associated with the mandibular injury [15]. The degree of symptoms such as edema, pain, and trismus depends on the force delivered to the face and the extent of inflammation associated with the trauma, resulting in varying levels of these clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…A study on 249 patients with a unilateral mandibular fracture showed no significant difference in a complication risk between patients treated by open reduction internal fixation with manual reduction or arch bar placement [13]. In a prospective study on 83 patients treated for unilateral mandibular fractures with maxillomandibular fixation, Anyanechi and Saheeb showed that posttraumatic pain and trismus are associated with the onset of complications [15]. Their study emphasized the influence of inflammation-mediated symptoms on the complications after closed reduction—an approach which is unable to estimate the influence of surgical trauma on postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The mandibular body fracture was chosen for investigation as it is the most common mandibular fracture in the study community. 10,[12][13][14] This study was exempted from ethical clearance by the Regional Ethics Committee of the University of Calabar Teaching Hospital Calabar, Nigeria (Reference No. UCTH/ HREC/33/584) because of its retrospective design and on the condition that the research data are not shared.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…As a result, the timing of treatment of mandibular fractures and its outcome has remained a contentious issue in oral and maxillofacial surgery practice as the optimal treatment delay for minimizing complications remains unknown. [8][9][10] Evidence suggests that there is heterogeneity and no consensus on the definition of "early" versus "delayed" treatment for patients with mandibular fractures, and the majority of studies do not make a definitive recommendation for early or delayed treatment. 4,8,9,11 Consequently, it is essential to determine if there is an optimal time for the treatment of mandibular fractures that mitigates the risk of post-operative complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation